A case of post-traumatic orbital cellulitis caused by Eikenella corrodens - Ni He; Zhenyu Peng (BMC Ophthalmology)
Abstract Background This study documents a rare instance of post-traumatic orbital cellulitis attributed to Eikenella corrodens. It underscores the significance of precise identification of this pathogen and prompt management of orbital cellulitis. Case presentation A 59-year-old male presented with a 3-day history of redness, swelling, and pain in his left eye, accompanied by increased secretions for 1 day after exposure to terrazzo ingredients. Initially diagnosed with left orbital cellulitis, he was treated with intravenous cefuroxime for 3 days without symptom improvement. Treatment was then shifted to intravenous ceftazidime and ornidazole, and secretions were cultured. As symptoms worsened, the patient underwent ultrasound-guided puncture and aspiration of the left orbital abscess, followed by cavity irrigation. This resulted in reduced eyelid swelling and secretions. Culture results confirmed the presence of Eikenella corrodens. Antibiotics were subsequently switched to intravenous amoxicillin-clavulanate potassium, but symptoms relapsed. A second debridement with drainage strip placement led to symptom resolution within 4 days, and the patient was discharged with amoxicillin-clavulanate tablets. Conclusions This report details a unique case of orbital cellulitis due to Eikenella corrodens infection. The treatment strategy, combining targeted antibiotics with ultrasound-guided abscess management, proved effective.